Hungarian Monitoring, 6 July 1989 . [Magyar rádiófigyelő], 1989. július 6 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev-Mitterrand talks: changes occurring in Poland and Hungary are the exclusive concern of those countries - Surprisingly light judgment in North case - Soviet evaluation of 56, 68 and developments today - Gorbachev's address today in Strasbourg Domestic Affairs: - János Kádár has died - How have the man on the street and wider world reacted to János Kádár's death? - Irony of fate: János Kádár dies on the same day as Hungary's highest court absolves October 1956 premier and colleagues, later executed, from all charges against them - Three-sided national roundtable holds further meeting - Hungarian Army carries out unilateral reduction in personnel numbers and arms - Austria donates ATS 1 million in aid to Romanian refugees in Hungary Külpolitika: - A Lengyelországban és Magyarországon zajló változások kizárólag a két népre tartoznak - Hangzott el Gorbacsov és Mitterrand megbeszélésén - North meglepően enyhe ítélete - Szovjet értékelés 56-ról, 68-ról, ill. a mai fejleményekről - Gorbacsov mai felszólalása Strasbourgban Belpolitika: - Meghalt Kádár János - Hogyan reagált az utca embere és a világ Kádár János halálhírére? - A sors iróniája: Kádár János ugyanaz nap halt meg, amikor a magyarországi legfelsőbb bíróság felmentette 1956 októberének később kivégzett miniszterelnökét és társait az ellenük felhozott vádak alól - Újabb ülést tartott a háromoldalú nemzeti kerekasztal - A Magyar Néphadsereg egyoldalúan létszám és fegyverzetcsökkentést hajt végre - Ausztria 1 millió schillinges segélyt ad a Magyarországon tartózkodó román menekülteknek